ANALYSIS OF THE EFFECTIVENESS OF FLY ASH AND BOTTOM ASH (FABA) WASTE UTILIZATION ON THE RATE OF PLANT VEGETATIVE GROWTH - Yusriani Sapta Dewi; Endah Rahayu Restini (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2026)
A coal-fired power plant is a type of power generation facility that uses coal as its primary fuel. During the power production process, both B3 (hazardous) and non-B3 waste are generated. One of the main types of waste produced is fly ash and bottom ash (FABA). When FABA is allowed to accumulate over a long period, it can cause environmental problems such as air and water pollution and a decline in ecosystem quality. The results of the FABA characteristic test using the Toxicity Characteristic Leaching Procedure (TCLP) showed that none of the tested parameters exceeded the quality standards, particularly for heavy metals, in accordance with Government Regulation Number 22 of 2021 concerning the Implementation of Environmental Protection and Management. This study examines the use of FABA as a growing medium for chili plants (Capsicum frutescens). The research employed visual observation and soil analyzer methods. Visual observations focused on plant growth indicators, including plant height and number of leaves, while soil analyzer was used to measure pH, moisture, and temperature. The treatment consisting of 75% FABA and 25% soil was found to be the optimal composition, producing the highest plant height and number of leaves up to the 10th week of observation. Furthermore, soil analyzer revealed that this combination is suitabie as a planting medium.